Financial Knowledge and "Don't Know" Response. Issue 4 (14th August 2019) - Kim, Namhoon; Mountain, Travis P.
Abstract : We investigate the effect of group characteristics and educational interventions on young respondents' objective financial knowledge level. We examine six questions about personal finance and covariates selected from the 2015 National Financial Capability Study. Because these questions include "Don't Know" or "Refuse" (DK/RF) responses, a simple regression model could cause researchers to reach misleading conclusions if DK/RF responses are not random. Thus, we suggest a binomial‐latent regression model to evaluate the effect of educational interventions and group differences that are hidden in DK/RF responses. The estimation result shows that rejecting financial education opportunities is disadvantageous to obtaining proper financial knowledge. In addition, both formal and informal financial education are less effective in improving objective financial knowledge in our preferred model. We also find few or no gender, income, and age differences in young adults' objective financial knowledge level after controlling for financial education interventions.